Effect of hCG application on day 12 post-mating on the reproductive efficiency and plasmatic concentrations of progesterone in hair ewes - Quintero, Juan; Olguín, H.; Quezada, A.; Janacua, H.; Rivas, R.; Macías, U. (Cuban Journal of Agricultural Science, 2016)
The application of human chorionic gonadotropin on day 12 postmating on the reproductive efficiency and plasmatic concentrations of progesterone in hair ewes submitted to an estrus synchronization program was assessed. Twenty four hair ewes were treated with vaginal sponges for 12 d and one application of 200 IU of PMSG at sponge removal. On day 12 post-estrus, ewes were injected with a saline solution (control group) or 300 IU of hCG (hCG group). Hormonal concentrations were determined in each female group. Blood samples were collected 2 h before and 0, 2, 4, 6, 8, 24 and 48 h after the beginning of the hCG application for the P4 analysis. The pregnancy diagnostic was realized 30 d post-mating. The pregnancy rate, lambing and fertility rates were analyzed through X2 and an analysis of variance was used for prolificacy. Treatment effects on plasmatic concentrations of P4 were determined by the analysis of repeated measurements using the SAS (2004) program. The hCG increased pregnancy rate compared to the control group (81.8 vs. 63.6 %; P < 0.001) and in the same way fertility was favored with hCG application (81.8 vs. 54.6 %; P < 0.001). There was significant difference (P < 0.001) in P4 plasmatic concentrations between treatments, being higher in ewes treated with hCG. Considering the results conclusions can be drawn that hCG administered on day 12 post-mating increases pregnancy rate, besides increasing the fertility of the treated ewes. The hCG also provokes significant increases in the progesterone plasmatic concentrations (P4) of female sheep. Key words: hCG; ewes, progesterone, fertility